2016
DOI: 10.17843/rpmesp.2016.332.2170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia del síndrome de burnout en médicos y enfermeras del Perú, Ensusalud 2014

Abstract: a Estudiante de medicina; b médico salubrista Recibido: 12/01/2016 Aprobado: 20/04/2016 Citar como: Maticorena-Quevedo J, Beas R, Anduaga-Beramendi A, Mayta-Tristán P. Prevalencia del síndrome de burnout en médicos y enfermeras del Perú, Ensusalud 2014. Rev Peru Med Exp Salud Publica. 2016;33(2):241-7. RESUMENObjetivos. Estimar la prevalencia del síndrome de burnout (SB) en los médicos y enfermeras del Perú en el año 2014, según los diferentes puntos de corte establecidos en la literatura. Materiales y métodos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
3
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 23 publications
(20 reference statements)
2
13
3
18
Order By: Relevance
“…Santiago-Ullero et al 31 found in 2015 that 4.9% of the sample of physicians and nurses living in Lima Metropolitana had the intention to migrate to the interior and that there was an association between perceived stress and the intention to migrate. Marticorena et al 32 found a global prevalence of job burnout of 2.8% using predetermined values; of 7.9% for cut points according to quartiles; and 12.5%, using tertiles. This phenomenon is not exclusive of Peru.…”
Section: Professional Discomfort and Stressmentioning
confidence: 99%
“…Santiago-Ullero et al 31 found in 2015 that 4.9% of the sample of physicians and nurses living in Lima Metropolitana had the intention to migrate to the interior and that there was an association between perceived stress and the intention to migrate. Marticorena et al 32 found a global prevalence of job burnout of 2.8% using predetermined values; of 7.9% for cut points according to quartiles; and 12.5%, using tertiles. This phenomenon is not exclusive of Peru.…”
Section: Professional Discomfort and Stressmentioning
confidence: 99%
“…Para el presente estudio se consideró solo el cuestionario dirigido a los profesionales de la salud (médicos y enfermeras) del Perú durante el año 2014, con una población total de 5067 12 . Se excluyó a 5 personas por no haber llenado de forma correcta el MBI-HSS 5 .…”
Section: Diseño Y Población De Estudiounclassified
“…En el Perú, en general, la prevalencia global del SB en los profesionales de la salud es 12,5 % (5) , aunque diferentes estudios nacionales presentan resultados heterogéneos (6,7) . En Ancash, específicamente, una investigación en personal sanitario de 10 hospitales reportó un porcentaje de burnout alto que oscila entre 19,6 % a 27,6 % (8) .…”
Section: Introductionunclassified